Gelatinous transformation of bone marrow in a rabbit. (November 2021) - Alonso, Flavio H.; Tarbert, Danielle K.; Wu, BinXi; Rodriguez, Paula; Christopher, Mary M.
A 9-y-old, spayed female rabbit was presented for evaluation of hypoglycemia and lateral recumbency. The patient was hypothermic and had diffuse muscle wasting; weight loss since a previous visit was also noted. Hematologic abnormalities included progressive nonregenerative anemia and severe heteropenia. Evaluation of a bone marrow aspirate sample revealed active hematopoiesis with abundant pink matrix. The matrix material stained positively with periodic acid–Schiff and alcian blue, and a diagnosis of gelatinous transformation of the bone marrow (GTBM, serous atrophy of fat) was made. Although its precise prevalence remains to be determined, GTBM should be suspected in rabbits with persistent cytopenias following prolonged starvation or gastrointestinal disease.